2009
DOI: 10.1002/cne.21891
|View full text |Cite
|
Sign up to set email alerts
|

The mesopontine rostromedial tegmental nucleus: A structure targeted by the lateral habenula that projects to the ventral tegmental area of Tsai and substantia nigra compacta

Abstract: Prior studies revealed that aversive stimuli and psychostimulant drugs elicit Fos expression in neurons clustered above and behind the interpeduncular nucleus that project strongly to the ventral tegmental area (VTA) and substantia nigra (SN) compacta (C). Other reports suggest that these neurons modulate responding to aversive stimuli. We now designate the region containing them as the mesopontine rostromedial tegmental nucleus (RMTg) and report herein on its neuroanatomy. Dense mu opioid receptor and somatos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
561
5
11

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 421 publications
(616 citation statements)
references
References 96 publications
39
561
5
11
Order By: Relevance
“…Jhou et al (2009a) recently showed that aversive stimuli induce Fos expression in VTA-projecting RMTg neurons, and phasically stimulate their electrical activity in behaving rats. Notably, a substantial number of VTA-projecting RMTg cells receive a major afferent from the LHb (Jhou et al, 2009b), thus corroborating the idea that RMTg might signal aversive events and inhibit midbrain DA neurons. Hence, in vivo we first tested the responses of putative RMTg neurons to a standard aversive somatosensory stimulus (hindpaw mechanical stimulation), which is known to exceed the threshold of pain in freely moving animals (Cahusac et al, 1990).…”
Section: Electrophysiological Characterization Of Rmtg Neuronssupporting
confidence: 69%
See 4 more Smart Citations
“…Jhou et al (2009a) recently showed that aversive stimuli induce Fos expression in VTA-projecting RMTg neurons, and phasically stimulate their electrical activity in behaving rats. Notably, a substantial number of VTA-projecting RMTg cells receive a major afferent from the LHb (Jhou et al, 2009b), thus corroborating the idea that RMTg might signal aversive events and inhibit midbrain DA neurons. Hence, in vivo we first tested the responses of putative RMTg neurons to a standard aversive somatosensory stimulus (hindpaw mechanical stimulation), which is known to exceed the threshold of pain in freely moving animals (Cahusac et al, 1990).…”
Section: Electrophysiological Characterization Of Rmtg Neuronssupporting
confidence: 69%
“…The i.p. injection of ( + ) methamphetamine hydrochloride (10 mg/kg in 0.9% saline; 1 ml/kg) given 2 h prior killing was used to produce Fos expression in the RMTg, as previously described by Jhou et al (2009b). See Supplementary Materials and Methods for detailed information.…”
Section: Stimulation Of Rmtg Fos Expression and Immunofluorescent Stamentioning
confidence: 99%
See 3 more Smart Citations